Pengaruh Pemanasan Bahan Bakar Dengan Memanfaatkan Aliran Oli Mesin Terhadap Kinerja Mesin Sepeda Motor - Triwibowo, Nur Akhmad (SENATIK STT Adisutjipto, 2017)
The increase of transportation need affects an increase in the need for fuel oil. The high fuel consumption can be controlled by refining the combustion process in the combustion chamber, one of them is by heating up the fuel. It could be one way to save fuel. The tests conducted on the Yamaha Jupiter MX assemblied in 2011 on the power, torque and fuel consumption by heating and without heating the fuel. Thevariations of engine speed used were 5000 rpm, 6000 rpm, 7000 rpm and 8000 rpm. The results indicated that the fuel heating through helical coil heat exchangers with oil fluid could increase the average power (7.03%) and the average torque (5.83%) at 6000 rpm - 8000 rpm and decrease the average spesific fuel consumption (17.13%) at 6000 rpm - 8000 rpm